Evaluating the Impact of Different Methods of Pre-Processing on Fermentation Capability and Physicochemical Properties of Oat Okara - Bilic,Lovro (2025)
Three different processing methods of raw oat okara were used in order to determine which method will have the highest impact in eliminating unwanted microorganisms and making the okara acceptable for human consumption. Processed okara was also fermented to determine the impact of processing technique on its fermenting capabilities and to develop a starting material for a sustainable and functional food product. Okara samples from various stages were tested for their phytic acid content, protein content, LAB count and spore count. In the end, it was found that autoclaving produced the highest number of LAB and had the highest protein count. All of the fermentations were successful, but the spore count produced unreliable results. Phytic acid results showed that HPP lowered the phytic acid levels the most, while sterilized samples had the highest levels of phytic acid. Despite some unexpected results, the project has been deemed a success as okara was fermented to provide a functional prebiotic starting material for foodstuffs.
Keywords: Fermentation; oats; foodstuffs; probiotic; waste; lactic acid bacteria; phytic acid; biotechnology